A Detailed Analysis of the Association between Urate Deposition and Erosions and Osteophytes in Gout - Pecherstorfer, Caroline; Simon, David; Unbehend, Sara; Ellmann, Hanna; Englbrecht, Matthias; Hartmann, Fabian; Figueiredo, Camille; Hueber, Axel; Haschka, Judith; Kocijan, Roland; Kleyer, Arnd; Schett, Georg; et al. (ACR Open Rheumatology, 2020)
ObjectiveTo characterize in detail the structural bone changes associated with the deposition of monosodium urate crystals in the first metatarsophalangeal (MTP1) joint in patients with tophaceous gout.
CRIS-Team WoS Importer:2021-07-16

A LONGITUDINAL DUAL ENERGY COMPUTED TOMOGRAPHY STUDY ON THE EFFECT OF URATE LOWERING THERAPIES ON THE REDUCTION OF TOPHUS BURDEN IN PATIENTS WITH CHRONIC GOUT - Ellmann, Hanna; Bayat, Sara; D'Oliveira, I.; Englbrecht, Matthias; Araujo, E.; Mendonca, S.; Lell, Michael; Manger, Bernhard; Schett, Georg; Rech, Jürgen; Cavallaro, Alexander Josef (2016)
EVALuna2:13439

Effects of Conventional Uric Acid-Lowering Therapy on Monosodium Urate Crystal Deposits - Ellmann, Hanna; Bayat, Sara; Guilhon de Araujo, Elizabeth; Manger, Bernhard; Kleyer, Arnd; Cavallaro, Alexander; Lell, Michael; Schenker, Hannah; Simon, David; Tascilar, Koray; Baraf, Herbert S. B.; Schett, Georg; et al. (Arthritis and Rheumatology, 2019)
Objective Few studies have systematically and quantitatively addressed the impact of urate-lowering therapy on monosodium urate (MSU) deposits. This study was undertaken to analyze the effect of lifestyle measures and conventional urate-lowering therapy on MSU deposits in patients with gout. Methods In this prospective study, subjects with gout according to the American College of Rheumatology/European League Against Rheumatism classification criteria and presence of MSU deposits seen on dual-energy computed tomography (DECT) scans received either lifestyle intervention or conventional urate-lowering therapy for a mean period of 18 months before a follow-up DECT scan. Detected MSU deposits were quantified by volumetric measurement and validated by semiquantitative scoring, and baseline and follow-up measurements were compared. Results Baseline and follow-up DECT scans were available for all 83 subjects. Six subjects discontinued treatment, and 77 subjects underwent a lifestyle intervention (n = 24) or were treated with allopurinol (n = 29), febuxostat (n = 22), or benzbromarone (n = 2) over the entire observation period. The mean serum uric acid (UA) level decreased from 7.2 to 5.8 mg/dl in the overall population. In patients who discontinued treatment, no change in MSU deposits or serum UA levels was observed. The burden of MSU deposits significantly decreased in patients undergoing lifestyle intervention (MSU volume P = 0.007; MSU score P = 0.001), and in patients treated with allopurinol (MSU volume and score P < 0.001) or febuxostat (MSU volume P < 0.001; MSU score P = 0.001). No significant decline in MSU deposits was noted in patients who discontinued treatment. Conclusion These data show that lifestyle intervention and xanthine oxidase inhibitors significantly decrease the MSU deposit burden. Hence, conventional gout therapy not only lowers serum UA levels, but also reduces pathologic MSU deposits.
CRIS-Team WoS Importer:2019-12-20

FINE STRUCTURE ANALYSIS OF THE INTER-RELATION BETWEEN TOPHUS DEPOSITION AND BONE LESIONS IN GOUT USING A COMBINATION OF DUAL ENERGY AND HIGH-RESOLUTION CT - Bayat, Sara; Simon, David; Pecherstorfer, Caroline; Ellmann, Hanna; Figueiredo, C.; Englbrecht, Matthias; Hueber, A.; Kleyer, Arnd; Rech, Jürgen; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

SIZE MATTERS - EXTENT OF MONOSODIUM URATE DEPOSITS BUT NOT SERUM URATE LEVEL PREDICTS COMPLETE RESOLUTION OF MONOSODIUM URATE CRYSTAL DEPOSITS IN PATIENTS WITH GOUT - Bayat, Sara; Ellmann, Hanna; Guilhon de Araujo, Elizabeth; Manger, Bernhard; Hagen, Melanie; Kleyer, Arnd; Lell, Michael; Schenker, Hannah; Simon, David; Tascilar, Koray; Baraf, Herbert S. B.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12